Щодо питання про можливість договірного регулювання адміністративних відносин - Завальна, Ж.В. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Possibility of establishing of the connections in administrative relations on the contractual basics is being considered in this article. Administrative relations entering in the complement of the object of the administrative law regulation were analyzed. The conclusion has been made that not all administrative relations which entering in the complement of the object of the administrative law regulation can be regulated by a contractual method. Only relations which in the nature contain the voluntary concordance of the expressions of will which generating right and duties can be regulated by a contractual method.